2015
DOI: 10.3389/fimmu.2015.00218
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Brazilian Anti Schistosomiasis Vaccine Based on the Recombinant Fatty Acid Binding Protein Sm14 Plus GLA-SE Adjuvant

Abstract: Data herein reported and discussed refer to vaccination with the recombinant fatty acid binding protein (FABP) family member of the schistosomes, called Sm14. This antigen was discovered and developed under a Brazilian platform led by the Oswaldo Cruz Foundation, from the Health Ministry in Brazil, and was assessed for safety and immunogenicity in healthy volunteers. This paper reviews past and recent outcomes of developmental phases of the Sm14-based anti schistosomiasis vaccine addressed to, ultimately, impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 41 publications
2
49
0
5
Order By: Relevance
“…Previous studies have found that GLA-SE, formulated with the recombinant fatty acid binding protein Sm14, enhances Th-1 type responses. Production of IFN-γ was the basis of Sm-14-mediated protective immunity both in humans with schistosomiasis and animal models (40). This Sm14 antischistosome vaccine is safe and entering phase 2 trials in Brazil and Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that GLA-SE, formulated with the recombinant fatty acid binding protein Sm14, enhances Th-1 type responses. Production of IFN-γ was the basis of Sm-14-mediated protective immunity both in humans with schistosomiasis and animal models (40). This Sm14 antischistosome vaccine is safe and entering phase 2 trials in Brazil and Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Compartmental model simulation of schistosomiasis transmission in endemic regions has predicted that, compared with MDA‐only programs, vaccination with a partially protective vaccine combined with MDA would be advantageous in reducing the acquisition of new worms and lowering egg release from residual worms in the environment . To date, there are three schistosomiasis vaccine candidates in various phases of human clinical trials: S. haematobium glutathione S ‐transferase (Sh28GST), S. mansoni tetraspanin, a 9‐kDa surface antigen (Sm‐TSP‐2), and S. mansoni 14‐kDa fatty acid‐binding protein (Sm14) …”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, Tendler and colleagues have demonstrated that the use of vaccines containing epitopes of the Sm14 protein could induce a level of protection similar to that observed with the recombinant protein. 8 This result indicates that the use of peptide may be a promising strategy in the development of new vaccines.…”
mentioning
confidence: 93%